PENERAPAN ALGORITMA C.45 UNTUK MEMPREDIKSI INDIKATOR WEBSITE YANG BAIK - rika Harman (Teknik Informatika, 2018)
The website for a company for now is not just a trend but it is a necessity that absolutely must not be, because with the website all the general information of the company can be shared to its customers directly tampa must be hampered by time and distance. as an example for a particular class of customers can find the information he wants without having to come directly keperusahaan. For that a website must contain important information about the company, the website should be able to represent customer service if asked by customers about company information related to customer needs. In this journal will be discussed one website of the company with 7 (seven) indicators, then of the seven indicators will be seen which indicators most influential on the website itself, this is certainly in the direction of customer satisfaction using the website. so it seems that the existing indicators have different effects between each other. To make this happen the researcher uses clustering method by using algortima C.45 with WEKA software version 44.02. The expected results will be to help the company in the process of developing a better website again.